Air Pollution Effects to the Subtype and Severity of Lung Cancers - Lee, Hung-Chi; Lu, Yueh-Hsun; Huang, Yen-Lin; Huang, Shih Li; Chuang, Hsiao-Chi (Frontiers in Medicine, 2022)
The correlation between lung cancer incidence and air pollution has been established in previous research, but the other detail impact of air pollution to lung cancer is still under investigation. This study aimed to explore if air pollution affected the subtype and staging of lung cancer. At the same time, we investigated the effect of individual pollutant to subtypes and staging. Single center data were extracted from January 1, 2020 to June 30, 2020 using the search engine in the radiology reporting system of Shuang-Ho Hospital, New Taipei City, Taiwan. There were 169 patients finally included for analysis. The nationwide statistics data of lung cancer were extracted from the Taiwan Cancer Registry. The air quality data were extracted from the Taiwan air quality monitoring network. Comparison of the single center lung cancer characteristics with nationwide data was made using the chi-square test. Comparison of the air quality of the living space of the included cases with the average quality in Taiwan in 2020 was made using the Z-test. The result shows there was significant difference of cancer subtype and staging between the regional data and the nationwide data. The regional data demonstrated a tendency of higher incidence of adenocarcinoma and advanced stage disease. As for air quality, there was no significant difference. The regional PM10 level presented generally lower levels in regional data as compared to Taiwan in 2020 with near statistically significant P-value (0.052); the regional NO2 level presented generally higher levels in regional data as compared to Taiwan in 2020 with near statistically significant P-value (0.060). The results indicate that air pollution might be related to increase in adenocarcinoma ratio and advanced stage of lung cancer at initial presentation. The NO2 was probably the leading pollutant causing this trend.